2019
DOI: 10.1002/ccd.28071
|View full text |Cite
|
Sign up to set email alerts
|

Small‐vessel PCI outcomes in men, women, and minorities following platinum chromium everolimus‐eluting stents: Insights from the pooled PLATINUM Diversity and PROMUS Element Plus Post‐Approval studies

Abstract: Objective We evaluated 1‐year outcomes after platinum chromium everolimus‐eluting stents (PtCr‐EES) in small versus non‐small coronary arteries within a large, diverse sample of men, women, and minorities. Background There exists limited outcomes data on the use of second‐generation drug‐eluting stent to treat small diameter coronary arteries. Methods We pooled patients from the PLATINUM Diversity and PROMUS Element Plus stent registries. Small‐vessel percutaneous coronary intervention (SV‐PCI) was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Of note, none of these studies used intracoronary imaging to determine vessel size before study inclusion, which might have contributed to the important observed differences between the vessel size-based inclusion criteria and actual reference vessel diameters (Tables 1 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and 2 [10][11][12][34][35][36][37] ).…”
Section: Recommendations For Standardized Definitions Of Small Vessel...mentioning
confidence: 99%
“…Of note, none of these studies used intracoronary imaging to determine vessel size before study inclusion, which might have contributed to the important observed differences between the vessel size-based inclusion criteria and actual reference vessel diameters (Tables 1 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and 2 [10][11][12][34][35][36][37] ).…”
Section: Recommendations For Standardized Definitions Of Small Vessel...mentioning
confidence: 99%
“…Historically, PCI in small vessels has resulted in an increase in adverse events 17 . However, several recent studies have reported no differences in clinical outcomes or angiographic measurements for small (RVD ≤2.5 mm) compared to non-small vessels after DES implantation, including no association of increased major adverse cardiac events (MACE) or TVR at 1 year 18 , no difference in early or late restenosis at 8 months 19 , and no difference in TLR at 2 years 20 for treatment in small vessels. Notably, favourable short-term outcomes were reported for a subsequent iteration of the R-ZES, the Resolute Onyx™ ZES (Medtronic), for patients with very small (RVD <2.25 mm) lesions: 5.0% TLF and 2.0% TLR at 1 year 21 , suggesting that advances in stent technology may ameliorate the performance of DES in small vessels after PCI.…”
Section: Discussionmentioning
confidence: 96%
“…Several definitions have been proposed for small vessel disease, including an angiographic reference vessel diameter of equal to or less than 2.75 mm or 2.5 mm ( 6 , 7 , 10 ). Despite variations in these definitions, small vessel disease has consistently been associated with an increased risk of adverse events, including restenosis and thrombosis ( 1 , 3 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study. small vessel coronary artery disease was defined as a minimal reference diameter ≤2.5 mm ( 6 , 7 ).…”
Section: Methodsmentioning
confidence: 99%